Development of an animal-borne blood sample collection device and its deployment for the determination of cardiovascular and stress hormones in phocid seals - Takei, Yoshio; Suzuki, Ippei; Wong, Marty K. S.; Milne, Ryan; Moss, Simon; Sato, Katsufumi; Hall, Ailsa (American Journal of Physiology-Regulatory, Integrative and Comparative Physiology, 2017)
The research was supported by Bilateral Program between Japan and the United Kingdom and a Grant-in-Aid for Scientific Research (23247010) to Y. Takei and by Grant-in-Aid for challenging Exploratory Research (15K14567) to I. Suzuki from the Japan Society for the Promotion of Science. This work was also supported by funding from the U.K. Natural Environment Research Council (Grant SMRU1001). An animal-borne blood sampler with data-logging functions was developed for phocid seals, which collected two blood samples for the comparison of endocrino-logical/biochemical parameters under two different conditions. The sampler can be triggered by preset hydrostatic pressure, acceleration (descending or ascending), temperature, and time, and also man-ually by light. The sampling was reliable with 39/50 (78%) successful attempts to collect blood samples. Contamination of fluids in the tubing to the next blood sample was 1%, following the prior clearance of the tubing to a waste syringe. In captive harbor seals (Phoca vitulina), the automated blood-sampling method was less stressful than direct blood withdrawal, as evidenced by lower levels of stress hormones (P < 0.05 for ACTH and P = 0.078 for cortisol). HPLC analyses showed that both cortisol and cortisone were circu-lating in seal blood. Using the sampler, plasma levels of cardiovascular hormones, atrial natriuretic peptide (ANP), AVP, and ANG II were compared in grey seals (Halichoerus grypus), between samples collected when the animals were on land and in the water. HPLC analyses determined that [Met12] ANP (1-28) and various forms of angiotensins (ANG II, III, and IV) were circulating in seal blood. Although water immersion profoundly changes the plasma levels of cardiovascular hormones in terrestrial mammals, there were only tendencies toward an increase in ANP (P = 0.069) and a decrease in AVP (P = 0.074) in the seals. These results suggest that cardiovascular regulation in phocid seals may have undergone adaptation during evolution of the carnivore to a ...